(3efGgL CYdGe GdfMh aj OGQ GdYdhe efP fTCJgG hMJi fgGjI GdbQf GdYTQjf (B: s (3OQGSI JMdjdjI (B/ s - (3aGWeI jSQj QTOj GdSjO LHQ s; (3CMeO eMeO YHOGdYRjR cTc (B: s ((3GdbGgQI (B: s (3aGWeI jSQj QTOj GdSjO LHQ (B: s, 2017)
(3gPG HMK Mhd efGgL CYdGe GdfMh aj OGQ GdYdhe efP fTCJgG hMJi fgGjI GdbQf GdYTQjf(B: (3GTJed Ydi ebOeI Yf (B((3eOQSI OGQ GdYdhe(B): (3hJegjO PcQJ ajg bGFeI ddfMhjjf HOGQ GdYdhe JHkYG dSfrj JNQLge MJi nerf MUd Ydi GdOcJhQGg aj GdfMh bHd YGe (B2000(3e(B. (3hGfbSe GdHMK Edi CQHYI aUhd YQVJ ajgG CQHYI efGgL aj OQGSI GdfMh ef NdGd CTgQ CYdGegG(B: (3hCge eG bOehg ef CacGQ(B: (3hgj(B: ((3JjSjQ GdfMh(B): (3hefgL (B((3fbOj(B): (3hefgL (B((3GdfMh hGdEHOGY(B): (3hefgL (B((3JQGKj(B). s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh hGdUQa hGdYQhV s
(3UOQ GjVG cbQU eOeLs
Keywords: (3efgL GddZI hGdEHOGYs; (3efgL JjSjQ GdfMh s; (3efgL fbOj s